Auditory closed-loop stimulation of EEG slow oscillations strengthens sleep and signs of its immune-supportive function. Issue 1 (December 2017) - Besedovsky, Luciana; Ngo, Hong-Viet; Dimitrov, Stoyan; Gassenmaier, Christoph; Lehmann, Rainer; Born, Jan
Abstract Sleep is essential for health. Slow wave sleep (SWS), the deepest sleep stage hallmarked by electroencephalographic slow oscillations (SOs), appears of particular relevance here. SWS is associated with a unique endocrine milieu comprising minimum cortisol and high aldosterone, growth hormone (GH), and prolactin levels, thereby presumably fostering efficient adaptive immune responses. Yet, whether SWS causes these changes is unclear. Here we enhance SOs in men by auditory closed-loop stimulation, i.e., by delivering tones in synchrony with endogenous SOs. Stimulation intensifies the hormonal milieu characterizing SWS (mainly by further reducing cortisol and increasing aldosterone levels) and reduces T and B cell counts, likely reflecting a redistribution of these cells to lymphoid tissues. GH remains unchanged. In conclusion, closed-loop stimulation of SOs is an easy-to-use tool for probing SWS functions, and might also bear the potential to ameliorate conditions like depression and aging, where disturbed sleep coalesces with specific hormonal and immunological dysregulations. Circulating hormones undergo fluctuations during sleep. Here, the authors increase electroencephalographic slow oscillations (SO) during sleep in men using an auditory closed-loop stimulation, and show that the circulating level of cortisol, aldosterone and immune cell count can be altered.